International Business and the Crisis of Globalization - A. Yu. Borisov (Vestnik MGIMO-Universiteta)
The author’s focal point is the interconnection and interdependence of geopolitics and business and corporate interests of modern states, primarily great powers in the new post globalized political and economic world order. Growing crisis of globalization has set up new rules of the game of market forces as a result of emerging new centers of state power, both in Europe and in Asia at the expense of «indispensable» America. American decay has become the buzz – word in academic community on both sides of the Atlantic. On «The Self Destruction of American Power» and on how «Washington squandered the Unipolar Moment» for example elaborates Fareed Zakaria, well known columnist and the author of «Post – American World». The question raised and answered in the article is how successfully international business adapts to new conditions of post globalization world and more fragmented marketplace. According to the author corporate interests in a way have become hostage to perilous geopolitical designs and protectionist strategies. The present Trump administration concerned by the rise of China and other competitors wages trade wars against both friends and foes more often than not at the expense of American businesses. The old Marxist dogma and economic determinism that «economics dictates politics» is not valid anymore under the new conditions of strengthening geopolitical rivalry of major world powers and their fighting for supremacy in international politics without due regard for specific business gains or losses. The United States being the only superpower is doing its utmost to stay the course of global hegemony and raises stakes for higher geopolitical risks at the expense of transnational business interests. Its relationships with China and Russia referred to by Washington as «revisionist powers» are at the forefront of the research. The key question to be answered as a result of the offered narrative is whether international cooperation or confrontation today plays a key role from the perspective of corporate “bottom line”.